2009
DOI: 10.1073/pnas.0906556106
|View full text |Cite
|
Sign up to set email alerts
|

Dual requirement for the ETS transcription factors Fli-1 and Erg in hematopoietic stem cells and the megakaryocyte lineage

Abstract: Fli-1 and Erg are closely related members of the Ets family of transcription factors. Both genes are translocated in human cancers, including Ewing's sarcoma, leukemia, and in the case of Erg, more than half of all prostate cancers. Although evidence from mice and humans suggests that Fli-1 is required for megakaryopoiesis, and that Erg is required for normal adult hematopoietic stem cell (HSC) regulation, their precise physiological roles remain to be defined. To elucidate the relationship between Fli-1 and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 28 publications
3
76
0
2
Order By: Relevance
“…We therefore investigated potential interactions between LMO2 and FLI1 in human T-ALL. ERG was included in this analysis as it has been shown that FLI1 and ERG, which is closely related to FLI1, may coregulate common target genes in haematopoietic stem cells and megakaryocytes (Kruse et al, 2009) and high ERG expression has recently been shown to predict adverse outcome in T-ALL (Baldus et al, 2006(Baldus et al, , 2007Bohne et al, 2009). ChIP using antibodies to ERG and FLI1 in Molt4 (LMO2-expressing non-translocated human T-ALL cell line) was therefore performed.…”
Section: Novel Lmo2 Promoter In Positive Feedback Loop In T-all Sh Ormentioning
confidence: 99%
“…We therefore investigated potential interactions between LMO2 and FLI1 in human T-ALL. ERG was included in this analysis as it has been shown that FLI1 and ERG, which is closely related to FLI1, may coregulate common target genes in haematopoietic stem cells and megakaryocytes (Kruse et al, 2009) and high ERG expression has recently been shown to predict adverse outcome in T-ALL (Baldus et al, 2006(Baldus et al, , 2007Bohne et al, 2009). ChIP using antibodies to ERG and FLI1 in Molt4 (LMO2-expressing non-translocated human T-ALL cell line) was therefore performed.…”
Section: Novel Lmo2 Promoter In Positive Feedback Loop In T-all Sh Ormentioning
confidence: 99%
“…ERG has a critical function in normal hematopoiesis. 16,17 It is also constitutively expressed in normal endothelial cells and regulates angiogenesis and endothelial apoptosis. [18][19][20] Several studies have shown anti-ERG antibody useful for prostate carcinoma, metastatic and primary, and prostatic intraepithelial neoplasias.…”
mentioning
confidence: 99%
“…It was previously demonstrated that SCL and EKLF promoted erythropoiesis, whereas ETS family members, such as ERG and FLI1, enhanced megakaryopoietic differentiation by inhibiting erythrocyte formation (Kruse et al, 2009;Starck et al, 2010). We found that both SCL and EKLF increased the expression of miR-144/451, whereas FLI1 downregulated miR-144/451, in turn miR-144/451 might target FLI1 to inhibit its expression in erythrocytes, thus forming a negative feedback circuitry to fine-tune the formation of red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Data were represented as mean±SE of replicates from at least three independent experiments. *, P<0.05; **, P<0.01; ***, P<0.001. ropoiesis mainly upregulated miR-144/451 and miR-142, whereas FLI1 and ERG, the key factors in megakaryocyte formation (Kruse et al, 2009), significantly increased the expression of miR-142 and miR-146b ( Figure 4A-D), implicating distinct roles of their target miRNAs during primitive hematopoiesis.…”
Section: Figurementioning
confidence: 99%